Onychoscopy with red light for vascular pattern identification: a study of 33 patients. (30th July 2019) - Pellacani, G.; Alessandrini, A.; Mandel, V.D.; Martella, A.; Brandi, N.; Chester, J.; Piraccini, B.M.; Starace, M.
Abstract: Background: Nail dermoscopy (onychoscopy) during physical examination assists in correct diagnosis. Often further magnifications are necessary for an effective differential diagnosis. With the addition of a red light to the dermoscope, important vascular features can be visualized. Objective: To describe common features observed at onychoscopy with a new device that combines the regular white light with the red light illumination, demonstrating that it is useful for diagnosis of nail disorders. Methods: We enrolled 33 consecutive patients referred to the Nail Diseases Dermatology Unit of the University of Modena and Reggio Emilia and to the Outpatient Consultation for Nail Disease of the Dermatology Unit of the University of Bologna. Patients were assessed with a standard hand‐held dermoscope and at the red light dermoscope. Dermoscopic images were collected. Results: The new prototype was used during daily clinical practice and allowed a more accurate visualization of some details that classic onychoscopy can miss. In particular, with the help of the red light it was possible to better visualize nail lesions that were characterized by some kind of colour change or vascular alterations. Conclusion: The new device of red light for vascular pattern onychoscopy can be a new investigation method to observe nail alterations, especially due to vascular pattern, even with low magnification, without the necessity to use higher resolutions.